2003
DOI: 10.1086/367929
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of A New Class of Pulsating Stars: Gravity-Mode Pulsators among Subdwarf B Stars

Abstract: During the course of an ongoing CCD monitoring program to investigate low-level light variations in subdwarf B (sdB) stars, we have serendipitously discovered a new class of low amplitude, multimode sdB pulsators with periods of the order of an hour. These periods are more than a factor of ten longer than those of previously known multimode sdB pulsators (EC 14026 stars), implying that they are due to gravity modes rather than pressure modes. The longer period pulsators are found only among cooler sdB stars, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(63 citation statements)
references
References 28 publications
2
61
0
Order By: Relevance
“…Green et al (2003) published the discovery of pulsations in V1093 Her, with periods between one half and two hours, and reported that as many as 75% of sdB stars cooler than 30 kK display some level of pulsations at these periods. The V1093 Her stars span the EHB from the coolest sdBs at around 24 kK up to the domain of the V361 Hya stars (Fig.…”
Section: Asteroseismologymentioning
confidence: 99%
“…Green et al (2003) published the discovery of pulsations in V1093 Her, with periods between one half and two hours, and reported that as many as 75% of sdB stars cooler than 30 kK display some level of pulsations at these periods. The V1093 Her stars span the EHB from the coolest sdBs at around 24 kK up to the domain of the V361 Hya stars (Fig.…”
Section: Asteroseismologymentioning
confidence: 99%
“…The analyses for the three pulsators estimate the convection zone to extend out to M cc = 0. 22 [14]. In the last case two equally probable solutions were found.…”
Section: Subdwarf B Starsmentioning
confidence: 88%
“…The short periods of the EC 14026 stars [10] are of the order of minutes and have amplitudes of a few tens mmag, while the longer periods in the PG 1716 stars [11] range from 30 to 80 mins at even lower amplitudes of a few mmag. Typical light curves are compiled in Fig.…”
Section: Pulsating Subdwarf B Starsmentioning
confidence: 99%
“…Only a fraction of the sdB stars with otherwise identical effective temperature, surface gravity and photospheric metallicity are pulsators; they co-exist with non-variable stars in the same region of the HRD and fall into two groups, the short-period p-mode and the longer-period g-mode prototype [11] (V 1093 Her)…”
Section: Pulsating Subdwarf B Starsmentioning
confidence: 99%